Venantius Fortunatus : personal and political poems - Venantius Fortunatus, asi 550-asi 600 (Translated texts for historians ;, 1995)
Venantius Fortunatus, writing in the latter half of the sixth century, was not only a major Latin poet, but also an important historical figure. He travelled as a young man to seek patronage in the courts of Merovingian Gaul, writing both formal and informal poetry for three of the royal brothers, Sigibert, Charibert and Chilperic, and for many influential figures in ecclesiastical and secular life. His poems paint a picture of a literary, not merely literate, culture, which complement’s Gregory’s canvas of bloodthirsty dynastic feuding.